13C-NMR Spectrometric Identification of Acid Hydrolysed Hydroxypropyl Starch Components - Haryadi Haryadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1991)
The products of acidic hydrolysis of hycroxypropyl starch (molar substitution 0.28) were isolated by HPLC using an amine treated μ Poracilcoloumn. Based on the 13C-NMR Spectral data the Individual fractions were assigned 1,2-0-[1.2-(S)-propyiene]-a-Dglucofuranose, 12-0-[1 ,2-(R) and (S)-propylene]-a-D-glucopyranose, 2-0-[2-hydroxypyl-(R) and (S)]-α,B-D-glucopyranose, and 6-0-[2-(R) and (S)-hydroxypropyI]-α,B-D-glucopyranose, respectively.